ICT AS A COMPONENT OF PREPARATION OF THE FUTURE ELEMENTARY SCHOOL TEACHERS TO CONDUCT EDUCATIONAL RESEARCH - Andrievskiy Б.М.; Вінник, Т.О. (Journal of Information Technologies in Education (ITE), 2015)
Article devoted to the mechanism of formation of research competence of future primary school teachers. Illuminated by a hierarchical system of assumptions implementing person-centered paradigm to improve research competencies of future teachers in primary education. Revealed organizational-pedagogical conditions of successful development of the ability of graduates of higher educational establishments in research professional activity by including students in targeted scientific research through lectures and seminars, independent and group work, the potential of research activities, teaching practice and specialist courses research orientation.